أغران الثرب الشحمية المترافقة بكيسات ثربية (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر أغران الثرب الشحمية المترافقة بكيسات ثربية من الحالات النادرة والتي تتواجد عادة بعد العقد الخامس من العمر وهذا ما أكدته دراستنا خلال 6سنوات (1996-2001) في مشفى الأسد الجامعي في اللاذقية على خمس حالات . تتميز هذه الآفة سريرياً بنموها السريع وكبر  حجمها الذي قد يصل أحياناً إلى 10 كغ، إذ تملأ كامل جوف البطن مما تسبب أعراضاً انضغاطية وحس ثقل وشد في البطن بالإضافة إلى تمدد بطن شديد، لكنها لا تسبب تدهوراً سريعاً في الحالة العامة للمريض يتناسب مع نموها السريع، كما أنها لا تدخل المريض في حالة الدنف السرطاني بشكل يتناسب مع نمو الورم بل على العكس من ذلك إذ يلاحظ تحسننا ملحوظاً في الحالة العامة للمريض بإزالة الضغط ولو كان هذا التحسن مؤقتاً لعدة أشهر شرط أن لا تتم إزالة الضغط الناجمة عن الكيسات الثربية ببزلها عن طريق جدار البطن خوفاً من حدوث الوفاة الآنية أثناء إجراء البزل بسبب انفجار الكيسة ودخول المريض مرحلة الصدمة والوهط الدوراني وهذا ما حصل في واحدة من حالاتنا السريرية المدروسة. The omental liposarcoma associated with omental cysts are considered rare cases. They usually exist after 5th decade of age, which is confirmed in our study at AL Assad Hospital in Lattakia on 5 cases during the period from (1996-2001). This lesion is clinically characterized by fast growth and large size which sometimes reaches 10 KGS, and fills the abdominal cavity and causes rapid compression symptoms as well as a sense of overweight and tension in the abdomen, besides intensive abdominal distention. This lesion doesn’t cause rapid decline in general condition of the patient despite its fast growth. Moreover the patient doesn’t suffer of carcinous cachexia associated with to the growth of the tomor. On the contrary, clear amelioration of general condition is seen by decompression of omental cysts. Per cutameous punction of the cysts, as a method for decompression is not recommended, this kind of punction might cause sudden death, shock and circulation callaps, which happened to one of our patients.